eBay e-Commerce Platform Opportunities and Obstacles - et. al., Yousef A. Baker El-Ebiary, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
E-commerce blends more than just electronics and commerce. It is an entirely new way of doing business through a medium that modifies the very rules of doing business. Therefore, it is much more about policy and organisation management than about technology. The success of a business comes from internal and external collective action and management of contact. There are various amounts of existing e-commerce platforms such as eBay, Amazon, BigCommerce, and more. eBay have been chosen as an e-commerce platform for a further study related to this topic. The objective of this case study is to explore the term of the opportunities and threads that also face the strength and weaknesses of eBay as one of the big e-commerce platforms. In order to explore this topic, a SWOT analysis on this platform needed. Analysing the strengths, weaknesses, opportunities, and threats is one of the most essential measures in managing an organisation.